Risk factors for early development of cardiac allograft vasculopathy by intravascular ultrasound. Issue 11 (22nd October 2020) - Moayedi, Yasbanoo; Fan, Chun Po S.; Tremblay-Gravel, Maxime; Miller, Robert J. H.; Kawana, Matsaka; Henricksen, Erik; Parizo, Justin; Wainwright, Rebecca; Fearon, William F.; Ross, Heather J.; Khush, Kiran K.; Teuteberg, Jeffrey J.
Abstract: Background: Cardiac allograft vasculopathy (CAV) is the leading cause of late graft loss. While there are numerous post‐transplant factors which may increase the risk of the development of CAV, there is a paucity of data on the impact of donor‐derived atherosclerosis (DA), early discontinuation of prednisone, and early initiation of proliferation signal inhibitors (PSI) as assessed by intravascular ultrasound (IVUS). Methods: Retrospective single‐center study of all adult transplant patients (2008‐2017) with serial IVUS at baseline and annually for 5 years. DA was defined as a baseline maximal intimal thickness (MIT) ≥0.5 mm, and CAV development was defined as MIT ≥1 mm or an increase in MIT ≥0.5 mm at year 1 compared with baseline or an increase in 0.3 mm annually thereafter. Clinical risk factors for CAV were identified using multivariable hazard regression. Separate multistate models were applied to assess the association of prednisone discontinuation and PSI initiation and CAV. Results: Of 282 patients screened, 186 patients had a 1‐year angiogram. The mean age of those included in the cohort was 51 ± 11 years, 70% were male, 58% were Caucasian, and 27% were supported by a left ventricular assist device. Donor atherosclerosis was present in 40%. The cumulative incidence of CAV at 5 years is 41% in DA‐ vs. 59% in DA + ( p  = .012). Donor age was a strong predictor of DA ( p  = .016). Significant risk factors for CAV included male sex (HR = 4.141, p  = .001), non‐Caucasian race (HR = 1.98, p  = .011), BMI < 18 kg/m2 (HR = 4.596, p  = .042), longer ischemic time (HR = 1.374, p  = .028), older donor age (HR = 1.158, p  = .009), and rejection with hemodynamic compromise within the first year (HR = 2.858, p  = .043). Prednisone discontinuation within 1 year was associated with a lower risk of CAV (HR 0.58 p  = .047). Initiation of proliferation signal inhibitors (PSI) within 2 years resulted in fewer cases of CAV (HR 0.397 p  < .001). Conclusion: In patients with an angiogram at 1 year, those with DA were significantly more likely to develop CAV. Lower incidence of CAV by IVUS was seen in patients who discontinued prednisone in the first year or had initiation of a PSI within two years of transplantation. Knowledge of early IVUS may allow a more tailored approach to patient management.